Resolution of Acute Hydrocephalus and Migration of Neurocysticercosis Cyst with External Ventricular Drainage - Abhineet Chowdhary; Taylor J. Abel; Patrik Gabikian; Gavin W. Britz (Case Reports in Medicine, 2010)
Neurocysticercosis is endemic in the developing world, but is becoming more common in the US due to immigration. A 24-year-old man presented with acute hydrocephalus and headaches, nausea, and vomiting. Head CT revealed a 3rd ventricular cyst and immunological studies were suggestive of neurocysticercosis. EVD placement resulted in migration of the cyst interiorly and superiorly with return of normal CSF flow by MRI and resolution of symptoms. Review of this condition is important given increasing incidence in the United States.